Do consumers buy less of a taxed good? - Hans Jarle Kind; Marko Köthenbürger; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper shows that consumers may buy more of a taxed good if it is sold by a two-sided platform firm. Two-sided platform industries serve distinct customer groups that are connected through interdependent demand, and include major businesses such as the media industry (newspapers/magazines and advertisers), banking (cardholder and merchant), and the software industry (users and application developers). The paper compares ad-valorem and specific taxes and shows that they may have opposite effects on quantities sold, and that the ad-valorem tax - the most commonly used tax throughout the OECD - has effects on prices and quantities not previously recognized.
Keywords: L13; H22; H21; D43; D4; 330; two-sided markets; ad-valorem taxes; specific taxes; Umsatzsteuer; Optimale Besteuerung; Konsumentenverhalten; Marktstruktur; Monopol; Ökonometrisches Modell